Employment and the Great Recession : The Role of Real Wages - Bakker, Bas (IMF Working Papers; Working Paper, 2015)
This paper argues that the sharp increase in unemployment in a number of advanced countries during the Great Recession was not just cyclical (the result of a lack of aggregate demand); the degree of adjustment of real wages and the impact this had on labor productivity also played a role. In many countries, post-2007 employment losses were modest, as real wages adjusted when the economy slowed down. But in some countries real wage growth stayed too high for too long. The result was large-scale labor shedding, which boosted labor productivity but also contributed to a sharp rise in unemployment. In this context, the paper discusses the different experiences of the UK (where employment increased) and Spain (where it fell sharply), and finds that almost two thirds of the employment losses in Spain resulted from the failure of real wages to adjust adequately.